Implementation the Role of Digital Technology to Financial Knowledge and Financial Behavior (Case Students STIE Nusantara Sangatta) - Mursalin, Andi; Riski, Meita Sondang; Asy’Ari, Sisca; Erduan, Muhammad; Indrawati, Andi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze implementation the role of digital technology to financial knowledge and financial behavior in case students STIE Nusantara Sangatta. This research uses quantitative research. This study uses a non-random sampling technique. The respondents in this study are STIE Nusantara Sangatta students, the number of samples in this study is 158 respondents. Methods of data collection is done by means of observation, questionnaires, and documentation. Data analysis in this study used multiple linear regression test analysis. The results show that financial knowledge has a positive and significant effect on digital financial technology transaction in case students STIE Nusantara Sangatta. Financial behavior has a positive and insignificant effect on digital financial technology transaction in case students STIE Nusantara Sangatta.